Impact of CSR on systematic risk across Chinese listed firms: mediating effect of technological innovation and moderating effect of ownership - Ru Duan; Suresh Ramakrishnan; Boon Keong Lim; Hishan Shanqer Sanil (Universitas Internasional Batam, 2023)
Firms’ capability to manage risk is increasingly important when the world economy is faced with more uncertainties. The impact of corporate social responsibility (CSR) on systematic risks remains inconsistent so far. By taking the unbalanced panel data of Chinese listed firms from 2010 to 2020, the paper uses 2SLS estimation to examine the relationship between CSR and systematic risks, explores the mediating effect of technological innovation and the moderating effect of ownership structure. It is found that that in context of China, the CSR engagement is negatively related to systematic risks. The effect is partially mediated by technological innovation. Moreover, the state-owned ownership structure positively moderates the negative impact of CSR on systematic risk. It is the few studies that uncover the mechanism through which CSR impacts systematic risk by discussing technological innovation as a mediator after addressing the complicated reverse causalities among CSR, technological innovation and systematic risk. These findings enrich the body of literatures on CSR and risk management, respond to the exploration of inconsistency in relationship between CSR and systematic risk and encourage the firms to be more proactively engaged in CSR practice and technological innovation. These long-perspective-oriented business practices decrease the systematic risk and benefit the sustainable development of firms.